FORMULATION AND EVALUATION OF POLYMERIC MICROSPHERES USING BOX–BEHNKEN DESIGN - NEELAM, SOMANI; MEENAKSHI, BHARKATIYA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The purpose of this research work was to formulate and systemically evaluate in vitro performances of polymeric microspheres of nifedipine. Methods: Nifedipine microspheres containing two polymers, poloxamer 407 and carbopol 934, were prepared by single emulsion cross-linking technique. Glutaraldehyde was selected as the cross-linking agent. A Box–Behnken design was employed to study the effect of independent variables, polymer concentration (X1), stirring speed (X2), and glutaraldehyde concentration (X3) on the dependent variables particle size, drug entrapment efficiency, and flow properties of microspheres. Results: Results of preliminary trials indicate that the polymer concentration, glutaraldehyde concentration, and stirring speed affected various characteristics of microspheres. The formulated Microspheres were discrete, spherical, and free flowing. The optimized batch exhibited with the narrow particle size of 75 μm, good flow properties, and drug entrapment efficiency of 96%. Conclusion: The polymeric microspheres of nifedipine with excellent flowability and good entrapment efficiency were successfully developed. These can be useful in improving patient compliance and bioavailability of nifedipine.